Left ventricular pseudoaneurysm associated with systemic lupus erythematosus. (April 2019) - Hoff, L S; Pimentel, C Q; Faillace, B L R; Rochitte, C E; Demarchi, L M M F; Bonfá, E; Seguro, L P C
Systemic lupus erythematosus (SLE) is associated with several cardiac manifestations but, to our knowledge, there have been no previously published reports on left ventricular (LV) pseudoaneurysm in this disease. We describe a case of a 30-year-old woman with SLE who presented with a disease flare (acute and subacute cutaneous lupus, pericarditis, fever, leukopenia) associated with heart failure syndrome. The patient was diagnosed with a large LV pseudoaneurysm and a bovine pericardium patch closure was performed. Coronary arteries were angiographically normal, and cardiac magnetic resonance imaging did not exhibit detectable myocardial fibrosis or infarction. Trauma, previous cardiac surgery, Chagas disease, and antiphospholipid syndrome were excluded. Histopathology of the pericardium revealed lymphocytic arteriolitis raising the possibility of an autoimmune-mediated mechanism for this complication. The unequivocal concomitant diagnosis of lupus flare, the exclusion of other causes of pseudoaneurysm and the histopathological finding of arteriolitis in this patient reinforces the hypothesis of lupus-mediated lesion.